Cell-free expression and SMA copolymer encapsulation of a functional receptor tyrosine kinase disease variant, FGFR3-TACC3 - Alexander J. D. Snow; Tharushi Wijesiriwardena; Benjamin J. Lane; Brendan Farrell; Polly C. Dowdle; Matilda Katan; Stephen P. Muench; Alexander L. Breeze (Scientific Reports)
Abstract Despite their high clinical relevance, obtaining structural and biophysical data on transmembrane proteins has been hindered by challenges involved in their expression and extraction in a homogeneous, functionally-active form. The inherent enzymatic activity of receptor tyrosine kinases (RTKs) presents additional challenges. Oncogenic fusions of RTKs with heterologous partners represent a particularly difficult-to-express protein subtype due to their high flexibility, aggregation propensity and the lack of a known method for extraction within the native lipid environment. One such protein is the fibroblast growth factor receptor 3 fused with transforming acidic coiled-coil-containing protein 3 (FGFR3-TACC3), which has failed to express to sufficient quality or functionality in traditional expression systems. Cell-free protein expression (CFPE) is a burgeoning arm of synthetic biology, enabling the rapid and efficient generation of recombinant proteins. This platform is characterised by utilising an optimised solution of cellular machinery to facilitate protein synthesis in vitro. In doing so, CFPE can act as a surrogate system for a range of proteins that are otherwise difficult to express through traditional host cell-based approaches. Here, functional FGFR3-TACC3 was expressed through a novel cell-free expression system in under 48 h. The resultant protein was reconstituted using SMA copolymers with a specific yield of 300 µg/mL of lysate. Functionally, the protein demonstrated significant kinase domain phosphorylation (t < 0.0001). Currently, there is no published, high-resolution structure of any full-length RTK. These findings form a promising foundation for future research on oncogenic RTKs and the application of cell-free systems for synthesising functional membrane proteins.